Pertumbuhan Bayi Usia 0-4 yang Mendapat ASI Eksklusif dan ASI Tidak Eksklusif = Infant Growth 0-4 Months with Exclusive... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstrak Exclusive breastfeeding can enhance optimal growth the infant. Quality infant foods or complementary foods give the infants in rural community is low, so the infant growth faltered occur in 1-6 month ages. The objectives of the study is to determine differences of infants growth, based on weight gain of the infants that give exclusive breastfeeding since 0-4 month and the infant that give partial breastfeeding. The design of this study was quasi experiment design and conducted in the rural area. Samples study were new born infants who met appropriate criteria and follow-up growth the infants since 0-4 month. In the end study the samples were divided into 2 groups, base on the infant feeding pattern. The groups were the infants received exclusive breastfeeding and partial breastfeeding. Total samples for exclusive breastfeeding were 110 and partial breastfeeding were 111. The morbidity data and infant feeding were collected in two weekly by recall method. The anthropometries data were collected every month. Data analysis using t-test, repeated measurement analysis of variance, c2, multiple linear regression. The result this study base on weight gain since the infants born until 4 month showed that the infants with exclusive breastfeeding higher than tose of infants with partial breastfeeding